Host-seeking behaviors of mosquitoes experimentally infected with sympatric field isolates of the human malaria parasite Plasmodium falciparum: no evidence for host manipulation - Vantaux, Amélie; de Sales Hien, Domonbabele F.; Yaméogo, Bienvenue; Dabiré, Kounbobr R.; Thomas, Frédéric; Cohuet, Anna; LEFEVRE, THIERRY (Frontiers in Ecology and Evolution, 2015)
Previous studies have shown that Plasmodium parasites can manipulate mosquito feeding behaviours such as motivation and avidity to feed on vertebrate hosts, in ways that increase the probability of parasite transmission. These studies, however, have been mainly carried out on non-natural and/or laboratory based model systems and hence may not reflect what occurs in the field. We now need to move closer to the natural setting, if we are to fully capture the ecological and evolutionary consequences of these parasite-induced behavioral changes. As part of this effort, we conducted a series of experiments to investigate the long and short-range behavioural responses to human stimuli in the mosquito Anopheles coluzzii during different stages of infection with sympatric field isolates of the human malaria parasite Plasmodium falciparum in Burkina Faso. First, we used a dual-port olfactometer designed to take advantage of the whole body odor to gauge mosquito long-range host-seeking behaviors. Second, we used a locomotor activity monitor system to assess mosquito short-range behaviors. Compared to control uninfected mosquitoes, P. falciparum infection had no significant effect neither on long-range nor on short-range behaviors both at the immature and mature stages. This study, using a natural mosquito-malaria parasite association, indicates that manipulation of vector behavior may not be a general phenomenon. We speculate that the observed contrasting phenotypes with model systems might result from coevolution of the human parasite and its natural vector. Future experiments, using other sympatric malaria mosquito populations or species are required to test this hypothesis. In conclusion, our results highlight the importance of following up discoveries in laboratory model systems with studies on natural parasite–mosquito interactions to accurately predict the epidemiological, ecological and evolutionary consequences of parasite manipulation of vector behaviors